A Pilot Study to Determine if Vitamin D Repletion Improves Endothelial Function in Lupus Patients. (October 2015) - Kamen, Diane L.; Oates, Jim C.
Abstract: Background: The endothelium is important not only in regulating vascular tone but also in modulating inflammation. Patients with systemic lupus erythematosus (SLE) have deficits in these endothelial functions. Vitamin D is a nuclear hormone that regulates vascular endothelial nitric oxide synthase activity and expression. Many SLE patients have insufficient levels of vitamin D. The effect of this hormone on vascular endothelial function in SLE patients is not known. This study was designed to determine the effect size of repleting vitamin D levels on endothelial function in patients with SLE and vitamin D deficiency. Methods: SLE patients with 25(OH) vitamin D (25(OH)D) levels <20 ng/mL were randomized to oral vitamin D3 (D3) doses that did or did not raise 25(OH)D levels to ≥32 ng/mL. Endothelial function was measured with flow-mediated dilation (FMD) before and after 16 weeks of vitamin D3 supplementation. Results: Half of those who achieved 25(OH)D levels of ≥32 ng/mL experienced increases in FMD, whereas none of those with continued low 25(OH)D levels did. Those with increases in FMD had significantly higher final 25(OH)D levels. Using the effect size from this study, future studies designed to test the effect of repleting 25(OH)D on FMD in vitamin D–deficient SLE patients will require 35 patients in each group. Conclusions: These results suggest a potential role for vitamin D in SLE-related endothelial dysfunction and that an adaptive, multi-arm, treat-to-target, serum-level trial design may increase the efficiency and likelihood of success of such a study.